Trilogi Kapabilitas Pemimpin Perspektif Al- Qur’an dalam Usaha Pengkolaborasian Tenaga Kependidikan - Khoirul Anwar; Sukarman Sukarman; Mariya Ulfah; Eva Ordiana (Jurnal Syntax Admiration, 2024)
This study aims to investigate a tripology of leader capabilities structured in three aspects namely, how a leader can respond, how a leader has the management abilityto respond so as to anticipate changes and how to control the work capacity of managers in the organization, so that the work carried out in every management, in particular educational management, can run as expected. This study uses qualitative method which the discussion source is obtained through a literature review methodology by collecting data in related literature. The results of the study reveal that social resources collabaration in educational field is an effective strategy that integrates professional collaboration, sustainable training, and shared leaarning to vercome challenges in education and to improve the quality of teaching. By educational staff collaboration, it allows teachers to meet. Share best practices, and adopt innovative methods which relevant to the needs of the current curriculum. In line to the Holly Qur’an which instructs educational staff to give maximum efforts by optimizing social resources in educational field.